Math Questions and Answers

Start Your Free Trial

How to solve this problem? Use the Laplace transform to solve the given initial value problem. y'' - 2y' +2y = 0; y(0)=1, y'(0)=0

Expert Answers info

hala718 eNotes educator | Certified Educator

calendarEducator since 2008

write3,662 answers

starTop subjects are Math, Science, and Social Sciences

`y'' - 2y' + 2y = 0 `

`=> L(y''-2y'+2y) = L (0) `

`==> L{y''}(s) - 2L{y'}(s) + 2{y}(s) = 0`

Now let `y(s)= L{y}(s) `

`==gt L{y'}(s)= sy(s) - y(0)= sy(s) - 1`

` ==gt L{y''}(s)= s^2 Y(s) - sy(0) -...

(The entire section contains 130 words.)

Unlock This Answer Now


check Approved by eNotes Editorial